2021
DOI: 10.33425/2639-9474.1192
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Saudi Mothers Cultural Practices related to Exclusive Breastfeeding during First Six Month of Infant Life

Abstract: Introduction: Around the world women breastfeed without question, there is a natural assumption that the breast will be offered to the newborn infant and that breast milk will nourish the infant until weaning. However, cultural beliefs and traditions passed down by the family and friends influences the mothers’ breastfeeding experience. Previous researches about breastfeeding in Saudi Arabia have been mostly using quantitative methods of research looking at rough numbers. Study Objective: Explore and describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This collaborative approach yields a total of five post-hospitaldischarge breastfeeding counseling intercepts. However, a qualitative study, although not generalizable, revealed that mothers in Al-Ahsa city do not experience this ideal approach lined out by the ministry [35]. Other studies in Saudi Arabia highlighted that postpartum breastfeeding knowledge was obtained from social media and online sources more than health care providers in postpartum health visits [11,15,19].…”
Section: Discussionmentioning
confidence: 96%
“…This collaborative approach yields a total of five post-hospitaldischarge breastfeeding counseling intercepts. However, a qualitative study, although not generalizable, revealed that mothers in Al-Ahsa city do not experience this ideal approach lined out by the ministry [35]. Other studies in Saudi Arabia highlighted that postpartum breastfeeding knowledge was obtained from social media and online sources more than health care providers in postpartum health visits [11,15,19].…”
Section: Discussionmentioning
confidence: 96%
“…Researchers from Arab countries have reported mixed feeding as a common feeding practice. 6,21,22,24,25 Supplementation with formula often starts around four months The most common reasons for mixed feeding were insufficient milk, return to work/ school, the belief that mixed feeding is the ideal method of feeding, and various breastfeeding difficulties. 21,22,29 Other studies reported difficulties in managing breastfeeding problems (eg, difficulty in positioning and latching, nipple soreness, pain, infection).…”
Section: Discussionmentioning
confidence: 99%
“…Religious teachings are reported as valuable sources of motivation that promote breastfeeding in this group of women. [6][7][8][9][10] Although Muslim Arab mothers are motivated to breastfeed from religious teaching, they often lack the knowledge of exclusive breastfeeding practices or hold cultural myths that hinder successful breastfeeding. [11][12][13] For example, prelacteal feeding (eg, water, sugar water, salt solution, crushed dates, artificial milk, animal milk, yogurt, gripe water, herbal tea, and black tea) is given for the first three days after delivery based on the belief that it cleanses the bowels of the newborn until the mother produces "white" milk.…”
Section: Introductionmentioning
confidence: 99%